2020
DOI: 10.3390/met10081067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of V–4Cr–4Ti Alloys from Mixed Oxides via Electro-Deoxidation Process in Molten Salt

Abstract: V–4Cr–4Ti alloys exhibit important advantages as a candidate structural materials for fusion reactor first-walls and blanket applications. V–4Cr–4Ti alloys were prepared by direct electrochemical reduction of the solid mixture of V2O3, Cr2O3 and TiO2 in the molten CaCl2–NaCl eutectic at 1073 K. The influence of cell voltage, sintering temperature and electrolysis time on the electrolysis process are reported. The microstructure and phase compositions of the products were analyzed by scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It shortens the process flow and significantly reduces energy consumption and environmental pollution. Meanwhile, considering the facile control of compositions (via raw materials) and reduction degree (via electrolytic voltage and time) of oxides, it is suitable for preparing functional materials [70–72] . For instance, manganese silicon alloy powders were successfully prepared by electro‐deoxidation [73] .…”
Section: Synthesis Of Silicon‐based Alloysmentioning
confidence: 99%
“…It shortens the process flow and significantly reduces energy consumption and environmental pollution. Meanwhile, considering the facile control of compositions (via raw materials) and reduction degree (via electrolytic voltage and time) of oxides, it is suitable for preparing functional materials [70–72] . For instance, manganese silicon alloy powders were successfully prepared by electro‐deoxidation [73] .…”
Section: Synthesis Of Silicon‐based Alloysmentioning
confidence: 99%
“…In comparison to the MOE method, this process achieves the direct electrolytic production of metals and alloys at lower temperatures ranging from 800 • C to 850 • C [19,20]. The use of solid metal oxides as cathodes in chloride molten salts for a direct electrochemical reduction to produce elemental metals has been applied in the extraction of various metals, including Fe [21,22], Ti [23], Cr [24,25], Al [26], V [27,28], Se [29], titanium-based [30][31][32][33][34], aluminum-based alloys [35,36], high-entropy alloys [37], etc. Research has shown that the addition of a small amount of CaO to CaCl 2 can significantly increase the rate of reduction and deoxidation [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the vanadium alloy has a better comprehensive performance when the content of Ti element and Cr element is about 3-5% (wt.%) [1][2][3]. V-4Cr-4Ti alloys exhibit important advantages as candidate structural materials for fusion reactor first walls and blanket applications [4,5].…”
Section: Introductionmentioning
confidence: 99%